Construct the Validity of STEM and Project-based Critical Thinking Skills Test Instruments Using the Rasch Model - Rina Dwi Setyawati; Binod Prasad; Agnita Siska Pramasdyahsari; Sindi Nur Aini (Phenomenon : Jurnal Pendidikan MIPA, 2023)
Students' critical thinking skills are very important abilities in the 21st century. To measure critical thinking skills, a valid and reliable instrument is needed. This article uses the Rasch model to construct an instrument for critical thinking skills on number pattern material whose learning uses STEM PjBL. The development method uses the analysis, design, development, implementation, and evaluation (ADDIE) stages. Data processing uses the Rasch model assisted by the Winstep program. The instrument was tested on 33 public junior high school students in Semarang. The research results include validity, namely the validity test by experts with an average percentage of 92.4% in the very valid category, the quality of the questions in the instrument reliability aspect is good, and the average critical thinking ability of students who use STEM-based and Project Based instruments Learning was 61.46, higher than other classes at 49.79. The critical thinking test instrument is based on STEM and the project needs to be further developed on other materials.Keywords: Construct Validity, Critical Thinking Skill, Rasch ModelKemampuan  berpikir kritis  siswa  merupakan  kemampuan  yang  sangat penting  di  abad  21  ini.  Untuk  mengukur  kemampuan  berpikir  kritis diperlukan instrumen yang valid dan reliabel. Tujuan penelitian ini adalah mengembangkan instrument tes kemampuan berpikir kritis yang berbasis STEM dan proyek. Soal terdiri dari 15 item materi aritmatika sosial yang memuat   indikator Focus,   Reason,   Inferent,   Situation,   Clarity   dan Overview. Metode pengembangan menggunakan tahapan analysis, design, development, implementation, and evaluation(ADDIE).Pengolahan data menggunakan  model Raschberbantuan  program Winstep.   Instrumen diujicobakan  pada  33  siswa  SMP  Negeri diSemarang.  Hasil  penelitian mencakup valid   yaitu   pada uji   validitas   oleh   ahli   dengan   rata-rata persentase sebesar 92,4 % dalam kategori sangat valid, kualitas butir soal pada aspek reliabilitas instrumen baik, dan  rata-rata  kemampuan berpikir kritis  siswa  yang  menggunakan  instrument  berbasis  STEM  danproyeksebesar  61,46  lebih  tinggi  dari kelas  lain sebesar  49,79.  Instrument  tes berpikir  kritis  didasarkan  pada  STEM  dan  proyek  perlu  dikembangkan lebih lanjut pada materi-materi lainya.